2014
DOI: 10.1158/1078-0432.ccr-13-1730
|View full text |Cite
|
Sign up to set email alerts
|

Improved Recurrence-Free Survival with ARCON for Anemic Patients with Laryngeal Cancer

Abstract: Purpose: Anemia is associated with poor tumor control. It was previously observed that accelerated radiotherapy combined with carbogen breathing and nicotinamide (ARCON) can correct this adverse outcome in patients with head and neck cancer. The purpose of this study was to validate this observation based on data from a randomized trial.Experimental Design: Of 345 patients with cT2-4 laryngeal cancer, 174 were randomly assigned to accelerated radiotherapy and 171 to ARCON. Hemoglobin levels, measured before tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 35 publications
(41 reference statements)
1
28
0
2
Order By: Relevance
“…This evidence should encourage us to move away from the common notion of transfusing patients with an Hb < 10 g/dl or a hematocrit (Hct) < 30%. Vaupel et al [31] found that an Hb level between 12 and 14 g/dl was optimal for tumor oxygenation even though no correlation has been found between Hb level and pO 2 [32, 33]. …”
Section: General Conditions Influencing Tumor Hypoxiamentioning
confidence: 99%
“…This evidence should encourage us to move away from the common notion of transfusing patients with an Hb < 10 g/dl or a hematocrit (Hct) < 30%. Vaupel et al [31] found that an Hb level between 12 and 14 g/dl was optimal for tumor oxygenation even though no correlation has been found between Hb level and pO 2 [32, 33]. …”
Section: General Conditions Influencing Tumor Hypoxiamentioning
confidence: 99%
“…The past decade has seen significant technological advances in investigating hypoxia imaging in radiation treatment planning and in providing us with the ability to individualize radiation delivery and target volume coverage. The presence of widespread hypoxia in the tumor can be effectively targeted with a systemic hypoxic cell cytotoxin or other agents that are more effective with diminished PO 2 , either alone or in combination 45 . Molecular imaging in general and hypoxia imaging in particular will likely become an important in vivo imaging biomarker of the future, complementing the traditional direct tissue sampling methods by providing a snap shot of a primary tumor and metastatic disease and in following treatment response and will serve as adjunct to personalized therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Carbogen breathing combined with radiotherapy has been successfully used in several clinical trials and has shown benefit in tumors with significant hypoxia 44 . It was the basis for the ARCON (Accelerated Radiotherapy with Carbogen and Nicotinamide) trial that was particularly beneficial in patients with signficant anemia 45 , resulting in better response and survival. Janssens et al found in a chort of 345 laryngeal cancer patients a better five-year disease free survival of 68% vs 45% (p = 0.04).…”
Section: Tumor Hypoxia and Clinical Outcomementioning
confidence: 99%
“…[44][45][46][47] Moreover, in this patient group, hypoxia-targeted interventions (e.g. nimorazole or nicotinamide combined with carbogen breathing) have shown promising results, [48][49][50] although the randomized trial of adding tirapazamine to cisplatin-containing CRT in the experimental arm failed to improve overall survival. 51 In considering the conduct of future combined-modality studies, this will increasingly highlight the dynamic nature of the tumour biology, for example, by including serial biomarker assessments during the course of fractionated radiotherapy to enable biological adaptation to changing tumour vulnerabilities, which will be further discussed below.…”
Section: Molecular Biomarkers Of Tumour Hypoxiamentioning
confidence: 99%